Effect of Dimethyl 2-(2-hydroxy phenyl amino)-3-(triphenyl phosphor anilidene)butanedioate on Corrosion Parameters of SS321 in C2H5OH-H2SO4 Solution - Mohammad Ali Hosseini, Seyed; Reza Islami, Mohammad; Mohammadi, Fatameh (Asian Journal of Chemistry, 2010)
Dissolution behaviour of stainless steel type 321 was studied in mixture of C2H5OH-H2SO4 solution using dimethyl 2-(2-hydroxy phenyl amino)-3-(triphenyl phosphor anilidene)butanedioate, [LOH], as inhibitor by potentiostatic method. The effect of temperatures (20–50±1ºC) on corrosion parameters of this alloy was investigated. The open circuit potential values in the presence and absence of [LOH] were noted before and after experiments that show a passive film is formed on the surface of the samples. The cathodic current density increased with increasing cathodic potential and temperature. The shapes of the cathodic curves are similar. The cathodic Tafel values ranged between (80–125 mV/dec I), indicating hydrogen evolution reaction taking place on the surface of the working electrode. In anodic region, active-passive behaviour was observed in all experimental solutions. The corrosion current density decreases with addition of [LOH]. The critical current density for passivation decreases with increasing [LOH] up to 10 ppm. Passivation current density and passivation potential vary irregularly with increasing concentration of [LOH]. The passive region vanished around 1100 mV and thereafter current density increased sharply. SEM taken from the surface of the sample after polarization reveals reduction of pits with using [LOH].